Ultrasensitive, light-induced reversible multidimensional biosensing using THz metasurfaces hybridized with patterned graphene and perovskite - Yao, Haiyun; Sun, Zhaoqing; Yan, Xin; Yang, Maosheng; Liang, Lanju; Ma, Guohong; Gao, Ju; Li, Tenten; Song, Xiaoxian; Zhang, Haiting; Yang, Qili; Hu, Xiaofei; et al. (Nanophotonics (Berlin, Germany), 2022)
Biosensors based on terahertz (THz) metasurfaces have recently attracted widespread attention. However, few have been reported so far because it is a challenge to achieve ultrasensitive multidimensional detection in the THz spectrum. Here, we propose a novel THz biosensor that consists of a metasurfaces and a metal oxide semiconductor-like structure (MOSLS), which is based on patterned graphene–polyimide–perovskite. We varied the photoconductivity of the MOSLS via the electrostatic doping effect. The biosensor could detect whey protein down to a concentration limit of 6.25 ng/mL. Significant responses in frequency, phase, and transmission amplitude were all detected for different protein concentrations. The transmission value difference, frequency shift, and phase difference increased with the concentration of whey protein, clearly demonstrating multidimensional biosensing. Moreover, by applying lasers with different wavelengths, we have realized reversible biosensing in THz region for the first time. These results are very promising for applications of THz metasurfaces in the field of biosensing.